Utilização dos métodos Vieta Jumping e Descida Infinita na solução de equações diofantinas e problemas envolvendo divisibilidade - Voelz, Marcia Eni (2018)
The dissertation explores the mathematical concepts and results of the Infinite Descent and Vieta Jumping methods for solving Diophantine equations and problems concerning divisibility. The main objective is to structure the results, proposing their proper use in the approach to classical problems and in the approach to problems of the International Mathematical Olympiads. The aim is to facilitate the use by students and teachers of programs such as OBMEP and PROFMAT, specially those involved in Mathematics Olympiads.